GENERATION MEAN ANALYSIS FOR ESTIMATION SOME GENETIC PARAMETERS FOR YILD AND YIELD COMPONENTS IN FOURE MAIZE CROSSES. - Hadi, B. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was conducted at the field of Field Crop .Dept., College of Agric\Univ.of Baghdad. spring and fall seasons of 2009, 2010 , spring of 2011 and fall of 2013 in order to know the relative magnitude of the genetic variation component and interactions forms of epistasis using Generation Means Analysis  of maize (Zea mays L.) . Six generations P1 , P2 , F1 , F2, BC1 and BC2 for four crosses (FI01301 Rustico), (AntignaoHi39× Nostred ) , (Lo1391 ×Rustico) and ( Rusticocangini× Rustico) were  evaluated by using randomized complete block design( RCBD) with four replications for grain yield and its components. The results showed significant differences between the generations of the four crosses. The first generation superiority and gave the highest mean for each of the traits of four crosses. The highest hybrid vigor and heterosis percent to  for unit area  grain yield (ton\ha) 121.8% and 126.92% for cross( FI01301 ×Rustico ). Most of the genetic effects  (d additive , dominance h , additive  × additive  i , additive × dominance j and dominance × dominance l) were significant for all crosses . This revealed  the importance of the dominance, additive and epistasis effects as genetic actions   controlled  in yield  inheritance and its components in maize. But the dominance variation was more important than the additive variation in the ear length  ,grain weighte and yield unit area, disagreement signal indicate the existence of an act of the dominance h and dominance× dominance  l of most studied traits duplicate epistasis. Supplementary superiority also appeared to Epistasis complementary of crosses (FI01301×Rustico) and (AntignaoHi39×Nostred) and grain weight in cross (Lo1391 ×Rustico ). It can be conclude that the additive and  non-additive gene action control the in heritable yield and its component . It is recommend using the method of reciprocal  recurrent selection(RRS) to improve yield and its components .